2023
DOI: 10.3390/rs15164072
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of Ecological Environment Based on Google Earth Engine Cloud Computing Platform and Landsat Long-Term Data: A Case Study of the Zhoushan Archipelago

Chao Chen,
Liyan Wang,
Gang Yang
et al.

Abstract: In recent years, with the rapid advancement of China’s urbanization, the contradiction between urban development and the ecological environment has become increasingly prominent, and the urban ecological system now faces severe challenges. In this study, we proposed an ecological index-based approach to monitor and evaluate the ecological environment using a Google Earth Engine cloud-based platform and Landsat time series. Firstly, a long-term series of Landsat images was obtained to construct and calculate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 131 publications
0
9
0
Order By: Relevance
“…The index, which quantifies the relative trend of a time series, was initially invented for the study of practical problems in water resources. Because the index can represent time series sustainability, it has been gradually utilized in the prediction studies of future ecological quality in recent years [34]. We calculated the Hurst index for the study area using a rescaled polarity (R/S) analysis.…”
Section: Sustainability Of Ecological Environment Qualitymentioning
confidence: 99%
“…The index, which quantifies the relative trend of a time series, was initially invented for the study of practical problems in water resources. Because the index can represent time series sustainability, it has been gradually utilized in the prediction studies of future ecological quality in recent years [34]. We calculated the Hurst index for the study area using a rescaled polarity (R/S) analysis.…”
Section: Sustainability Of Ecological Environment Qualitymentioning
confidence: 99%
“…Chen et al calculated the RSEI status of the Zhoushan Islands from 1985 to 2020 based on the GEE (Google Earth Engine) platform. Their analysis revealed that the overall ecological environment of the Zhoushan Islands showed a downward trend, but the RSEI values were concentrated, with small interannual fluctuations and relatively stable time-series [20]. Based on previous research [21,22], using the RSEI model for spatial long-term environmental monitoring and analysis can achieve significant results in WHKSs with fragmented terrain, wide regional scope, and strong contrast of human activity cold and hot spots.…”
Section: Introductionmentioning
confidence: 98%
“…RSEI and its improvements are widely used in the assessment and analysis of eco-environmental quality at different scales [12][13][14][15]. Meanwhile, the use of remote sensing cloud computing platforms, such as Google Earth Engine (GEE), greatly improves the efficiency of remote sensing data processing and analysis [16], which makes the application of large-scale and long time series RSEI more efficiently [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%